Questioning the Practice of State Capture Corruption in the Revision of the 2020 Mining Law - Dandi Jayusman; Muhammad Fathi (IHSA Institute, 2023)
This article examines the topic of state capture corruption and how Indonesia's Corruption Law treats the practice. This article also intends to look into the practice of state capture corruption in the Mineral and Coal Mining Law revision. This study was created using normative legal research methods from a statutory and conceptual standpoint. This will be followed by descriptive and qualitative analysis. The findings of this study lead to the conclusion that state capture corruption is a type of compromise between people in positions of power and employers to produce legislation that serves their commercial interests. Due to the limited definition of corruption, the Corruption Law struggles to address this issue. Also, the 2020 Mineral and Coal Mining Law revision exposed some measures that were made specially to advance the financial interests of entrepreneurs while simultaneously deleting provisions that provided such actors control